Students' Knowledge of Solubility Topics through The Cooperative Learning STAD Type - Ismi Nurlatifah; Wawan Wahyu; Wahyu Sopandi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
The topic of solubility is included in the chemistry subject matter that is considered difficult by students. This study aims to identify differences in knowledge improvement between the experimental class using the cooperative learning model STAD (Student Teams Achievement Divisions) type and the control class using the conventional learning model. The research method and design used is a quasi-experimental with nonequivalent control group design. The participants that involved in this study were students of class XI MIPA with 33 students for the experimental class and 32 students for the control class. A written test that has been validated is used as an instrument in this study. From the student scores that obtained, the N-Gain score is calculated, and hypothesis testing is done through SPSS. The results showed that there was a significant difference in increasing knowledge (p<0.05) between the experimental class (<g>=0.71) and the control class (<g>=0.54). The cooperative learning model STAD type is suitable to be applied for solubility topic learning. It can also be used for the others topic.